Ubiquitin-binding site 1 of pathogenic ataxin-3 regulates its toxicity in Drosophila models of Spinocerebellar Ataxia Type 3 - Prifti, Matthew V.; Libohova, Kozeta; Harris, Autumn L.; Tsou, Wei-Ling; Todi, Sokol V. (Frontiers in Neuroscience, 2023)
Spinocerebellar Ataxia Type 3 (SCA3) is a member of the family of polyglutamine (polyQ) diseases that are caused by anomalous CAG triplet repeat expansions in several genes. SCA3 results from abnormal polyQ expansion in the deubiquitinase (DUB), ataxin-3 (Atxn3). To understand the role of the different domains of mutant Atxn3 on its pathogenicity, with the hope that they can be explored for therapeutic interventions, we have systematically studied their individual and collective effects on its toxicity. One such domain is ubiquitin-binding site 1 (UbS1) on the catalytic domain of Atxn3; UbS1 is necessary for the enzymatic activity of Atxn3. Here, we investigated the importance of UbS1 on the toxicity of pathogenic Atxn3. We generated transgenic Drosophila melanogaster lines that express polyQ-expanded Atxn3 with and without a functional UbS1. We found that mutating UbS1 markedly exacerbates the toxicity of pathogenic Atxn3. Additional studies indicated that UbS1 regulates the toxicity of Atxn3 not by affecting its aggregation or sub-cellular localization, but by impacting its role in ubiquitin processing. Our findings provide additional insights into the role of Atxn3’s domains in the pathogenicity of SCA3.